Fire regimes and woody biomass dynamics in Australian savannas. (30th August 2013) - Murphy, Brett P.; Lehmann, Caroline E. R.; Russell‐Smith, Jeremy; Lawes, Michael J.; Parr, Kate
Abstract Aim Many tropical savannas are undergoing a trend of increasing woody biomass, or 'woody thickening'. Management to reduce fire frequency and intensity in savannas could substantially increase the amount of carbon stored in woody biomass. We addressed two questions: (1) are northern Australian savannas thickening; and (2) to what extent, and by what demographic processes, does fire affect woody biomass accumulation? Location Three large national parks, covering 24, 000 km2, in monsoonal northern Australia. Methods We examined changes in woody biomass carbon stocks – inferred from tree basal area and the density of woody understorey plants – over a 10‐year period in 136 savanna monitoring plots. We statistically assessed these changes in relation to fire frequency and severity. We used a meta‐analysis to identify general trends in woody cover in Australian savannas over the last half‐century. Results Woody biomass carbon stocks were relatively stable across the three national parks, but rates of change were statistically indistinguishable from earlier findings of a weak thickening trend. Change was negatively correlated with fire frequency, particularly the frequency of severe fires. High frequencies of severe fires decreased rates of accumulation of biomass by existing trees (through reductions in tree growth and death of individual stems), rather than whole‐tree mortality and suppression of recruitment. However, across northern Australia, our meta‐analysis identified a general, albeit weak, trend of woody thickening. Main conclusions The drivers of northern Australia's weak thickening trend are uncertain, but likely candidates include increasing atmospheric CO2 concentration and water availability, and pastoral intensification. We demonstrate that changes to fire management have the potential to either increase or decrease rates of woody thickening relative to any underlying trend. Understanding how savanna fires affect woody biomass, and how fire effects are mediated by climate and CO2, are essential research priorities to predict the fate of savannas.